Novel Ecranization of Santri Pilihan Bunda for Film Director Angling Sagaran and Lesson Plan - Zahro, Afrida Lailatul; Indriana, Nilna; Diantika, Devi Eka (Jurnal Pembelajaran Bahasa dan Sastra, 2025)
This study aims to describe: 1) the results of ecranization in the adaptation of the novel Santri Pilihan Bunda by Salsyabila Falensia into a film entitled Santri Pilihan Bunda directed by Angling Sagaran; 2) the procedure for planning the implementation of learning from the results of equalization in the adaptation of the novel Santri Pilihan Bunda by Salsyabila Falensia into a film entitled Santri Pilihan Bunda directed by Angling Sagaran using a constructivist approach and a copying task technique via the Google Form media with the file upload option. The focus of this study is to identify and explain the forms of reduction, addition, and changes in character aspects that occur during the equalization process and the implementation of the learning plan for students enrolled in the Literary Theory course. This study employs a qualitative descriptive method with a comparative literature approach, drawing on the organization theory proposed by Pamusuk Eneste. The research data for the organization adaptation of the novel Santri Pilihan Bunda by Salsyabila Falensia into a film entitled Santri Pilihan Bunda, directed by Angling Sagaran, is limited to the character aspect. The focus of the study is the reduction, addition, and change in character traits between the novel and the film. The results of the study showed: 1) there was a reduction of 13 novel characters in the film scene; there was an addition of 9 new characters in the film, and there were seven characters in the film who experienced a change in the role; 2) the procedure for planning the implementation of organization learning in the adaptation of the novel Santri Pilihan Bunda by Salsyabila Falensia into a film entitled Santri Pilihan Bunda directed by Angling Sagaran which used a constructivist approach and a copying task technique via the Google Form media with the file upload option for the Literary Theory course involved 27 core activities. This study contributes to understanding the organization of short stories into novels and contributes to the learning plan.